Active damping method for voltage source inverter-based distributed generator using multivariable finite-control-set model predictive control - Jonggrist Jongudomkarn; Warayut Kampeerawat (Institute of Advanced Engineering and Science, 2021)
Despite its advantages, the LCL filter can significantly distort the grid current and constitute a substantially more complex control issue for the grid-connected distributed generators (DGs). This paper presents an active damping approach to deal with the LCL filter's oscillation for the finite-control-set model predictive control (FCS-MPC)-three-phase voltage source inverters (VSIs)-based DG. The new approaches use the multivariable control of the inverter side's filter current and capacitor voltage to suppress the LCL filter resonance. The proposed method has been tested in steady-state and under grid voltage disturbances. The comparative study was also conducted with the existing virtual resistance active damping approaches for an FCS-MPC algorithm. The study validates the developed control schemes' superior performance and shows its ability to eliminate lower-order grid current harmonics and decrease sensitivity to grid voltage distortion.